Interactions of adjuvants on adhesion and germination of Isaria fumosorosea on adults of Diaphorina citri - Arnosti, Andre [UNESP]; Delalibera Junior, Italo; Conceschi, Marcos Roberto; D'Alessandro, Celeste Paola; Travaglini, Raphael Vacchi [UNESP]; Camargo-Mathias, Maria Izabel [UNESP] (Univ Sao Paolo, 2019)
Asian citrus psyllid, Diaphorina citri, is considered the most important citrus pest worldwide, as it transmits Huanglongbing - serious citrus disease. New efficient and sustainable strategies to control this pest have been investigated and the use of entomopathogenic fungi has become a promising alternative. The objective of this study was to evaluate the effects of adjuvants a) Tween 80 at 0.01 % (v/v); b) Silwet L77 at 0.025 % (v/v) and c) KBRAdj at 0.075 % (v/v) on adhesion, germination and pathogenicity of Iaaria fumosorosea ESALQ-1296 (5 x 10(6) conidia mL(-1)). Female adults of D. citri used in this experiment were sprayed on Citrus limonia seedlings. The sprayed insects were analyzed through scanning electron microscopy (SEM) to identify the most susceptible integument regions for fungus attachment and the effect of adjuvants used. In the pathogenicity test, adjuvants Silwet L77 and KBRAdj presented a higher efficiency than Tween 80. Fungi adhered predominantly to the ventral posterior (abdomen) region in comparison with the dorsal anterior (thorax) region. In addition, adjuvants Silwet L77 and KBRAdj presented faster germination (< 48 h) of f. fumosorosea spores when compared to Tween 80 (> 72 h). Conidial germination in the dorsal part of the thorax of the insects was observed only with adjuvant KBRAdj 72 h post inoculation.
Keywords: biological control; Asian citrus psyllid; entomopathogenic fungi; formulation; integument